Investigation of the Shape and Detectability of Pores with X-ray Computed Tomography - Benjamin Baumgärtner; Juan Hussein; Tino Hausotte (Journal of Manufacturing and Materials Processing, 2023)
Component porosity is a quality attribute in additive manufacturing (AM). One possibility for the non-destructive three-dimensional determination of porosity or pore shape is X-ray computed tomography (CT), which enables an investigation of the influence of AM process parameters on the appearance and characteristics of the pores. Since there is no porosity standard for CT, a traceable determination of the measurement uncertainty is not possible. Using a digital twin of the CT system, an estimation of the CT measurement uncertainty is in principle possible. In this contribution, experimental CT analyses of powder bed fusion samples made of Ti64 and PA12 are compared with CT simulations. The results show a size-dependent influence on the shape and detectability of the pores. Using the CT model, a simulated shape- and material-dependent probability of detection (POD) is calculated.